2022
DOI: 10.3390/su14031850
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Recreationist-Environment Fit Hospitality Experiences of Green Hotels in China

Abstract: To develop the hotel industry’s competitiveness, research on satisfaction and revisit intentions has always been important. More research has recently focused on guests’ pro-environmental behaviors and low-carbon management in the hotel industry. This research creates a recreationist-environmental fit satisfaction-revisit intention model based on the recreationist-environmental fit theory. This study surveyed seven green-standard hotels in Sanya, China, and tested the moderating effect of guests’ environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 163 publications
2
15
0
Order By: Relevance
“…In this study, we wanted to see if green certificates increased the likelihood of returning and paying a higher price for a hotel room. The structural model confirmed the positive and significant relationships between these variables, confirming the findings of previous studies such as this one: "Exploring Recreational-Environment Fit Hospitality Experiences of Green Hotels in China", written by Yu and published in the journal Sustainability in 2022 (Yu, 2022) [26]. Gu has also confirmed these findings in his article "The Effects of Subjective Knowledge, Altruistic Value and Consumer Self-Confidence on the Green Purchase Attitudes and Green Purchase Behaviour of Chinese Customers", which was published in 2022 (Gu, 2022) [32].…”
Section: Partial Least Squares (Pls)-structural Equation Modelling Mo...supporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we wanted to see if green certificates increased the likelihood of returning and paying a higher price for a hotel room. The structural model confirmed the positive and significant relationships between these variables, confirming the findings of previous studies such as this one: "Exploring Recreational-Environment Fit Hospitality Experiences of Green Hotels in China", written by Yu and published in the journal Sustainability in 2022 (Yu, 2022) [26]. Gu has also confirmed these findings in his article "The Effects of Subjective Knowledge, Altruistic Value and Consumer Self-Confidence on the Green Purchase Attitudes and Green Purchase Behaviour of Chinese Customers", which was published in 2022 (Gu, 2022) [32].…”
Section: Partial Least Squares (Pls)-structural Equation Modelling Mo...supporting
confidence: 85%
“…Most hotels take environmental conservation seriously and strive to reduce their environmental effect through ecologically friendly measures. A recent survey found that 55% of guests were willing to pay more for an ecologically friendly hotel room (Yu, 2022) [26]. Furthermore, 70% responded that choosing an ecologically responsible hotel would affect their decision to book a specific hotel for a vacation or business travel.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…Tourists who experience satisfaction when visiting a tourist site tend to have the desire to revisit that destination on different occasions. Within the context of tourism, tourists select destinations that possess characteristics capable of satisfying their needs (Stylos et al, 2017;Yu, 2022). According to research of the literature, tourists who demonstrate proenvironmental behavior and have a strong commitment to long-term environmental development goals will gain advantages from visiting natural tourist destinations (Shien et al, 2022).…”
Section: Revisit Intention To Eco-destinationmentioning
confidence: 99%
“…China did not realize that low-carbon environmental protection would become a new trend in the hotel industry until 2010. Since then, different scholars have studied the low-carbon production [ 28 ], low-carbon consumption [ 6 ], low-carbon service [ 29 ], low-carbon management [ 30 ], and low-carbon image [ 31 ] of the hotel industry and achieved great results. However, there are few studies on the spatial pattern, evolution trend, and income relationship of carbon emissions of Chinese hotels over a long time series.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%